2006
DOI: 10.1097/01.ta.0000202462.96207.18
|View full text |Cite
|
Sign up to set email alerts
|

Are Occult Pneumothoraces Truly Occult or Simply Missed?

Abstract: Less than 24% of all OPTXs might have been inferred from subtle radiologic findings, such as the deep sulcus sign. The majority of OPTX cases (50-64%) did not warrant a CT scan based on other findings. Concern for an OPTX after severe trauma is a valid indication for thoracic CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…9 However, CXR in humans increases risk of clinical deterioration in traumatized and intensive care patients, involves radiation exposure, incurs delay in diagnosis, and is prone to misinterpretation. [14][15][16]18,[19][20][21] In traumatized dogs and cats, CXR poses similar concerns. Transport to the radiology area, requiring physical movement and restraint of the patient, increases stress and oxygen demand, potentially compromising critically injured dogs and cats.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 However, CXR in humans increases risk of clinical deterioration in traumatized and intensive care patients, involves radiation exposure, incurs delay in diagnosis, and is prone to misinterpretation. [14][15][16]18,[19][20][21] In traumatized dogs and cats, CXR poses similar concerns. Transport to the radiology area, requiring physical movement and restraint of the patient, increases stress and oxygen demand, potentially compromising critically injured dogs and cats.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]14,[16][17][18]27,28,[31][32][33][34][35] Using computerized tomography (CT) as the gold standard, reports have documented the reliability of thoracic US to diagnose PTX in humans. 1,16,18,19,27 Moreover, human studies have shown thoracic US to be comparable in specificity (94% versus 100%) and superior in sensitivity (88-100% versus 36%-75%) to supine survey CXR, 1,15,16,27,[36][37][38][39][40] with CXR missing 30-50% of radiographically occult pneumothoraces. [14][15][16][17]40 US has been dubbed an 'extension of the physical exam' regarding intrathoracic fluid, in human critical care and trauma settings, because of its high sensitivity and specificity in detecting pleural and pericardial fluid compared with physical examination and CXR findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons associated with delayed diagnosis have been investigated, and include trauma severity, conditions that alter the process of attention, conditions that complicate the clinical evaluation, and errors in the process (Box 3) [147,152,154,163,164].…”
Section: Missed Injuries and Tertiary Surveymentioning
confidence: 99%